El aprendizaje del idioma kichwa y el fortalecimiento de la inclusión educativa en 10mo año de educación general básica de la Unidad Educativa Comunitaria Intercultural Bilingüe Guardiana de la Lengua y los Saberes Santiago de Guayaquil - Ilvis Yungan, Myrian Soledad (2018)
The work developed arises from a group of flaws, related to the learning of the Kichwa language, observed in an educational context during the teaching- educational process. Determining the need to investigate the possible alternatives to achieve progress in such a sensitive aspect, considering the possibilities that the knowledge of the original language contributes to educational inclusion, which, if not dealt with in time, would have an impact on the loss of traditions, culture and identity. For the theoretical and scientific sustenance of the investigation, it was necessary to investigate through several authors various terms related to the problem, or its correct understanding, through the documentary and bibliographical revision taking as references the current theories…….